Short‐acting anticholinergic bronchodilation does not increase cardiovascular events in smokers with mild to moderate pulmonary obstruction. Issue 4 (25th April 2013) - de, Emmy; van, Wouter D.; Heijdra, Yvonne; Lenders, Jacques W. M.; van, Chris; Akkermans, Reinier; Schermer, Tjard R. J.
Abstract Background and objective We hypothesized that bronchodilation in patients with chronic obstructive pulmonary disease (COPD) increases the smoke‐related risk to develop cardiovascular disease, and aimed to study the effect of short‐acting anticholinergic bronchodilation and smoking on cardiovascular events. Methods We performed a secondary analysis on data from the Lung Health Study, a large randomized clinical trial of smokers with mild to moderate pulmonary obstruction, 35–60 years old, without cardiovascular comorbidity. We used Cox proportional survival analysis, controlling for several confounders, to study the effect on 5‐year risk of fatal and/or non‐fatal cardiovascular events. Secondary outcome encompassed fatal and non‐fatal coronary events. Results Of 2745 participants, 23 (0.8%) died of cardiovascular disease. One hundred and sixty‐two participants were hospitalized for a cardiovascular event, and 94 participants due to a coronary event. Survival analysis revealed no effect between smoking and short‐acting anticholinergic bronchodilation on fatal and/or non‐fatal cardiovascular events, hazard ratio = 1.12 (0.58–2.19), nor on coronary events, hazard ratio = 1.46 (0.60–3.56). Conclusions Our study results show that short‐acting anticholinergic bronchodilation had no detrimental effect on cardiovascular disease in smokers with mild to moderate pulmonary obstruction.